Deviations from Triangular Arbitrage Parity in Foreign Exchange and Bitcoin Markets - Reynolds, Julia; Sögner, Leopold; Wagner, Martin (Central European Journal of Economic Modelling and Econometrics, 2021)
This paper applies recently developed procedures to monitor and date so-called “financial market dislocations”, defined as periods in which substantial deviations from arbitrage parities take place. In particular, we use a cointegration perspective to focus on deviations from the triangular arbitrage parity for exchange rate triplets. Due to increasing attention on and importance of mispricing in the market for cryptocurrencies, we include the cryptocurrency Bitcoin in addition to fiat currencies in our analysis. We do not find evidence for substantial deviations from the triangular arbitrage parity when only traditional fiat currencies are considered, but document significant deviations from triangular arbitrage parities in the newer market for Bitcoin. We tentatively confirm the importance of our results for portfolio strategies by showing that a currency portfolio that trades based on our detected break-points outperforms a simple buy-and-hold strategy.